Initiating heavy‐atom‐based phasing by multi‐dimensional molecular replacement. Issue 3 (1st March 2016) - Pedersen, Bjørn Panyella; Gourdon, Pontus; Liu, Xiangyu; Karlsen, Jesper Lykkegaard; Nissen, Poul
Abstract : A strategy is presented to set up an n ‐dimensional molecular‐replacement parameter matrix (MRPM) search using anomalous difference Fourier maps from related data sets to uncover weak, but correct, molecular‐replacement solutions for heavy‐atom substructure determination and subsequent experimental phasing. Abstract : To obtain an electron‐density map from a macromolecular crystal the phase problem needs to be solved, which often involves the use of heavy‐atom derivative crystals and concomitant heavy‐atom substructure determination. This is typically performed by dual‐space methods, direct methods or Patterson‐based approaches, which however may fail when only poorly diffracting derivative crystals are available. This is often the case for, for example, membrane proteins. Here, an approach for heavy‐atom site identification based on a molecular‐replacement parameter matrix (MRPM) is presented. It involves an n ‐dimensional search to test a wide spectrum of molecular‐replacement parameters, such as different data sets and search models with different conformations. Results are scored by the ability to identify heavy‐atom positions from anomalous difference Fourier maps. The strategy was successfully applied in the determination of a membrane‐protein structure, the copper‐transporting P‐type ATPase CopA, when other methods had failed to determine the heavy‐atom substructure. MRPM is well suited to proteins undergoing large conformational changes where multiple search models should be considered, and it enables the identification of weak but correct molecular‐replacement solutions with maximum contrast to prime experimental phasing efforts.